Forestry Vocabulary - Swedish Language Council, Institute for Language and Folklore (Institute for Language and Folklore, 2023)
Multilingual glossary containing terms related to forestry. The glossary has been produced in cooperation with the Swedish Forest association. The glossary contains 3512 terms in Swedish. Some of the terms are also translated to German, Finnish, Norwegian, Danish, Icelandic and English.

The glossary may be found at the path TNC 96 Skogsordlista/tnc96_imkand.txt in the archive TNC_ordlistor.zip.

Flerspråkig terminologisamling som rör skogstermer. Ordlistan har utarbetats av TNC i nära samarbete med Sveriges skogsförbund. Samlingen innehåller 3512 termer på svenska. Somliga termer är översatta till tyska, finska, norska, danska, isländska, och engelska.

Ordlistan finns på sökvägen TNC 96 Skogsordlista/tnc96_imkand.txt i filarkivet TNC_ordlistor.zip.
Skogsordlista
TNC 96
Keywords: forestry; skogsbruk; multilingualism; flerspråkighet; glossaries; ordlistor; terminology; terminologi; Swedish Centre for Terminology; Tekniska Nomenklaturcentralen; Languages and Literature; Språk och litteratur